Low-rate ferrate dosing damages the microbial biofilm structure through humic substances destruction and facilitates the sewer biofilm control. (15th May 2023) - Yan, Xiaofang; Sun, Jing; Wang, Yizhen; Zhang, Zisha; Zhang, Chuning; Li, Wei; Xu, Juan; Dai, Xiaohu; Ni, Bing-Jie
Highlights: Low-rate Fe(VI) dosing can cause the destructive effect on sewer biofilm structure. Fe(VI) mainly reduced HS in biofilm EPS thus leading to loosed biofilm structure. Key functional groups holding macromolecular of HS were more vulnerable to Fe(VI). Fe(VI) enhanced microbial interaction barriers so biofilms reduced mechanical stability. Fe(VI) enhanced inactivation effects of biocides on sewer biofilms with reduced cost. Abstract: The microbial activities in sewer biofilms are recognized as a major reason for sewer pipe corrosion, malodor, and greenhouse gas emissions. However, conventional methods to control sewer biofilm activities were based on the inhibitory or biocidal effect of chemicals and often required long exposure time or high dosing rates due to the protection of sewer biofilm structure. Therefore, this study attempt to use ferrate (Fe(VI)), a green and high-valent iron, at low dosing rates to damage the sewer biofilm structure so as to enhance sewer biofilm control efficiency. The results showed the biofilm structure started to crush when the Fe(VI) dosage was 15 mg Fe(VI)/L and the damage enhanced with the increasing dosage. The determination of extracellular polymeric substances (EPS) showed that Fe(VI) treatment at 15-45 mgFe/L mainly decreased the content of humic substances (HS) in biofilm EPS. This is because the functional groups, such as C-O, -OH, and C=O, which held the large molecular structure of HS, were the primary target of Fe(VI) treatment as suggested by 2D-Fourier Transform Infrared spectra. As a result, the coiled chain of EPS maintained by HS was turned to extended and dispersed and consequently led to a loosed biofilm structure. The XDLVO analysis suggested that both the microbial interaction energy barrier and secondary energy minimum were increased after Fe(VI) treatment, suggesting that the treated biofilm was less likely to aggregate and easier to be removed by the shear stress caused by high wastewater flow. Moreover, combined Fe(VI) and free nitrous acid (FNA) dosing experiments showed for achieving 90% inactivation, the FNA dosing rate could be reduced by 90% with the exposure time decreasing by 75% at a low Fe(VI) dosing rate and the total cost was substantially decreased. These results suggested that applying low-rate Fe(VI) dosing for sewer biofilm structure destruction is expected to be an economical way to facilitate sewer biofilm control. Graphical abstract: Image, graphical abstract